2015
DOI: 10.1161/circulationaha.114.014833
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Risk of Incident Atrial Fibrillation

Abstract: A trial fibrillation (AF) is the most common sustained cardiac arrhythmia, currently affecting >2 million people in the United States. 1 With an aging population, its prevalence is projected to double over the next 30 years. 2,3 The total health expenditures incurred by patients with AF are almost 5 times those of patients without AF, ranging between $6 and $26 billion.4 AF is also associated with considerable morbidity and mortality. 5 Although the management of AF has received much attention, literature furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(35 citation statements)
references
References 37 publications
4
29
0
2
Order By: Relevance
“…Light to moderate amounts of exercise seem to reduce AF risk, 13,15,16 and better cardiorespiratory fitness is shown to have a graded, inverse relationship to AF risk up to a certain point. 28,29 Our study results extend these previous findings by also showing a reduced burden of AF in individuals with manifest disease. This concept of AF treatment has not previously been reported, but other studies have shown that modification of risk factors reduces AF burden, 30,31 risk of new-onset AF, 32 and recurrence after ablation 33,34 and cardioversion.…”
Section: Discussionsupporting
confidence: 90%
“…Light to moderate amounts of exercise seem to reduce AF risk, 13,15,16 and better cardiorespiratory fitness is shown to have a graded, inverse relationship to AF risk up to a certain point. 28,29 Our study results extend these previous findings by also showing a reduced burden of AF in individuals with manifest disease. This concept of AF treatment has not previously been reported, but other studies have shown that modification of risk factors reduces AF burden, 30,31 risk of new-onset AF, 32 and recurrence after ablation 33,34 and cardioversion.…”
Section: Discussionsupporting
confidence: 90%
“…[2][3][4][5][6] However, the mechanism by which higher levels of CRF might lower stroke risk have not been well established, and it remains uncertain to what extent there may be a direct effect of CRF on stroke risk, independent of established stroke risk factors such as hypertension, diabetes mellitus (DM), and atrial fibrillation (AF). [7][8][9][10] Although previous studies evaluating the relationship between CRF/physical activity and risk of stroke adjust for the baseline risk factors, [3][4][5][6][7]11 they do not allow for the adjustment for subsequent, downstream risk factors acquired after CRF/physical activity measurement. Against this background, we linked the Cooper Center Longitudinal Study (CCLS) with individual claims data from the Center for Medicare and Medicaid Services (CMS) to better characterize the association between midlife CRF and stroke risk at a later age.…”
mentioning
confidence: 99%
“…Selvin shows in the National Health and Nutrition Survey (NHANES) that arterial hypertension is strongly correlated with PAD (Selvin and Erlinger, 2004). Rhythm disorders decrease the patient's biologic balance and affect the quality of life (Feringa et al, 2006;Qureshi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%